3D Analysis and Design of Al-Amal Hospital - Ahmad Jaber; Mosab Saabna; Laith Mahmoud; AmeenDaraghmeh (My University, 2014)
"AL-Amal Hospital" is to be constructed in Salem near Nablus. It consists of six stories, each one has a different area. The total area is 11000 m2 approximately .The design process included an architectural layout, structural framing options using both steel and concrete, roof systems and shear walls .The work is in compliance with the IBC and local building codes. Several structural materials and strategies will be evaluated to produce a final, cost-effective, design recommendation, which is presented in SAP Models.From a structural point of view the structural elements, footings, columns, beams, and slabs will be designed statically first by hand and using SAP, then dynamically by means of SAP. Finally, the effect of stiffness of foundation on the structural elements will be studied.Detailed sections of the structural elements showing the dimensions and the distribution of steel reinforcement will be introduced using AutoCAD.The design of the structure in this project was started by giving preliminary dimensions for the structural elements by using simple principles of structural design.The three dimensional modelling that done by SAP program is used to simulate the structure and all applied loads to obtain the final design for the structurePractical structural drawings shall be obtained based on the final results of the dimensional analysis and design.